Germany's expanding role in global health - Kickbusch, Ilona; Franz, Christian; Jahn, Albrecht (The lancet, 2017)
Summary Germany has become a visible actor in global health in the past 10 years. In this Series paper, we describe how this development complements a broad change in perspective in German foreign policy. Catalysts for this shift have been strong governmental leadership, opportunities through G7 and G20 presidencies, and Germany's involvement in managing the Ebola virus disease outbreak. German global health engagement has four main characteristics that are congruent with the health agenda of the Sustainable Development Goals; it is rooted in human rights, multilateralism, the Bismarck model of social protection, and a link between development and investment on the basis of its own development trajectory after World War 2. The combination of momentum and specific characteristics makes Germany well equipped to become a leader in global health, yet the country needs to accept additional financial responsibility for global health, expand its domestic global health competencies, reduce fragmentation of global health policy making, and solve major incoherencies in its policies both nationally and internationally.